An analysis of residential trip generation in Cape Town - Pas, Eric Ivan (Department of Civil Engineering, 2016)
Some of the factors contributing to the growth of a 'transportation problem' in Cape Town are outlined, and the main trends are illustrated. A brief introduction to the Urban Transportation Planning Process is presented, and the importance of the trip generation sub-model within the conventional traffic forecasting model is highlighted. A review of past and current practice in the analysis of residential trip generation is presented. The least-squares and category analysis techniques are compared, and the dummy variable method is briefly described. The unit of analysis to be used in the development of residential trip generation models is discussed. The independent variables frequently incorporated in models of residential trip-making are examined, and their effects on home-based trip generation are analysed. Some of the problems associated with the development of regression models are examined. The planning and execution of a home questionnaire survey of households in the Cape Town area is described.